Anti-inflammatory activity of Alpinia malaccensis (Burm. f.) roscoe and Kaempferia galanga L. rhizome essential oil gel formulations by carrageenan induction method - Muchtaridi, Muchtaridi; Abdullah, Derif A.; Suhandi, Cecep; Sumiwi, Sri A.; Nur Kusaira Khairul Ikram (Penerbit Universiti Kebangsaan Malaysia, 2022)
Bioactive compound from essential oils of Alpinia malaccensis (AM) and Kaempferia galanga (KG) rhizomes, respectively, such as methyl cinnamate and ethyl-p-methoxycinnamate (EPMS) have been reported to have anti-inflammatory activity. The present study aimed to determine the topical anti-inflammatory activity of 3 gel formulations (Formula 1, 2 and 3) having different concentrations of essential oil from AM and KG rhizomes. The gelling agent used in this study was Carbopol 934. The physicochemical parameters of the gel formulations such as organoleptic, pH, viscosity, and spreadability as well as hedonic test were also examined. The anti-inflammatory activity assay was carried out using the carrageenan induced rat paws edema method. The chemical composition of AM and KG rhizomes was identified by GC-MS with LRI index. The major essential oils content in AM and KG rhizome was methyl cinnamate (58.80%) and ethyl-p-methoxy cinnamate (59.68%), respectively. Based on the results of physical evaluation, hedonic test and anti-inflammatory activity, Formula 1 with 5% AM and 2.5% KG essential oils is the best formula with % inflammation inhibition of 36.32 ± 6.32%.